Governance role of auditors and legal environment: Evidence from corporate disclosure transparency - HAN, Sam (Institutional Knowledge at Singapore Management University, 2008)
This study examines whether auditor size associates with disclosure transparency. Given thatprior studies generally focus on discretionary accruals to investigate the relation betweenauditor size and financial reporting quality, there is little evidence on how auditor size relates toother attributes of reporting quality. Further, studies that examine this associationinternationally produce mixed results as to how auditor size relates to reporting quality indifferent legal origins. Focusing on corporate disclosure transparency (i.e., disclosure levels), wefind that auditor size and disclosure level are positively associated across countries and that theassociation is stronger in code law regimes than in common law regimes. The latter findingsupports the view that audits play greater governing roles in weaker legal environments.